Optogenetic restoration of retinal ganglion cell activity in the living primate - Juliette E. McGregor (Nature Portfolio, 2020)
Non-human primate models are important for the development of high quality vision restoration therapies for blindness. Here, the authors demonstrate restoration of light responses in foveal retinal ganglion cells of the living macaque following optogenetic gene therapy.